Sleep disturbance in patients taking opioid medication for chronic back pain - Robertson, J; Purple, R; Cole, P; Zaiwalla, Z; Wulff, K; Pattinson, K (John Wiley & Sons Ltd, 2016)
Poor sleep is an increasingly recognised problem with chronic pain and increases the impact of pain on daily function. To identify the impact of chronic pain and opioid analgesia on sleep quality, this study investigated activity and sleep patterns in patients taking opioid and non-opioid analgesia for chronic back pain.